Circularly Polarized Luminescence: Circularly Polarized Luminescence Induced by Chiral Super Nanospaces (Adv. Funct. Mater. 35/2019). (26th August 2019) - Kim, Byeong‐Cheon; Choi, Hyeon‐Joon; Lee, Jae‐Jin; Araoka, Fumito; Choi, Suk‐Won
Abstract : In article number 1903246, Fumito Araoka, Suk‐Won Choi, and co‐workers demonstrate circularly polarized luminescence (CPL) from a nanosegregated mesophase consisting only of achiral molecules. CPL is induced through self‐assembled chiral aggregates (in the chiral super nanospace) formed only by achiral molecules. The results introduce the possibility of developing a novel technique for constructing practical CPL active materials.